Self-help groups as sites of active citizenship: a qualitative study of the democratising role of self-help in the public sphere - Chaudhary, Sarah (2014)
Self-help groups in the United Kingdom continue to grow in number and address virtually every conceivable health condition, but they remain the subject of very little theoretical analysis. The literature to date has predominantly focused on their therapeutic effects on individual members. And yet they are widely presumed to fulfil a broader civic role and to encourage democratic citizenship. The thesis uses qualitative data derived from individual and group interviews with 33 groups in order to provide an outline of the ethos, aims, activities and structural arrangements of a broad range of self-help groups in Nottinghamshire, UK. It then uses these findings as the foundation on which to construct a model of self-help groups’ democratising effects in the public sphere and as a means of differentiating them from other types of ‘health citizenship’ organisation such as new social movements. In order to do this it broadly follows the work of Jurgen Habermas, making use of his concepts of communicative action; system-lifeworld integration; lifeworld autonomy and collective identity as an appropriate framework against which to account for these groups in civic terms.